Anticardiolipin antibodies are associated with cognitive dysfunction in stroke‐free individuals. (7th December 2013) - Homayoon, N.; Schwingenschuh, P.; Hofer, E.; Katschnig‐Winter, P.; Schmidt, R.
<x xml:space="preserve">Abstract</x> Background and purpose The presence of anticardiolipin antibodies (aCLs) has been associated with vascular occlusive events. The role of aCLs as a risk factor for stroke has been a matter of debate, and scarce information exists on the relationship between aCLs and other cerebral disorders. Reports exist for seizures, chorea and subtle cognitive dysfunction. The association between aCLs and cognition was further explored and the relationship between aCL titres and brain magnetic resonance imaging (MRI) findings was evaluated in a large cohort of community‐dwelling individuals. Methods The study cohort was drawn from the Austrian Stroke Prevention Study. A total of 1895 subjects had a complete risk factor assessment and measurement of aCL titres in serum. Participants were classified as aCL positive if either the immunoglobulin G (IgG) or IgM aCL titres were elevated (IgG > 21 U/ml, IgM > 12 U/ml). All subjects were also categorized based on the quartile distribution of IgG and IgM isotype titres. All underwent cognitive testing by the Mini Mental State Examination (MMSE) and a random sample of 947 participants also underwent brain MRI. Results aCL positive participants performed worse on the MMSE. IgG but not IgM isotype titres related to worse performance on the MMSE. No significant association existed with vascular brain abnormalities including lacunes, cortical infarcts and white matter lesions. Conclusions These data support the view that in normal elderly persons increasing IgG aCL titres relate to global cognitive dysfunction. It is unlikely that structural brain lesions are responsible for this finding.